Influence of fertilization in the formation of “moca” coffee beans and beans size - Laviola, Bruno Galvêas; Mauri, Aldo Luiz; Martinez, Hermínia Emilia Prieto; Araújo, Eduardo Fontes; Neves, Yonara Poltronieri (Coffee Science - ISSN 1984-3909, 2007)
Four Coffea arabica L. cultivars (Catuaí vermelho IAC-99, Icatú Amarelo IAC-3282, Rubi MG-1192 and Acaiá IAC- 474-19) were investigated in an experimental area to detect possible influence of fertilization in the formation of “moca” coffee beans and beans size, this determined by their retention in sieves numbered according to the diameter of their holes. Beans were collected at “cherry” stage of maturation. Fertilizers were added in a way that essay 1 received 40% of the recommended dose for essay 2 which received fertilization according to soil analysis; and essay three which received 1.6 times the dose recommended for essay 2. The experimental scheme was a 3 X 4 factorial (three fertilization levels and four cultivars) in a completely randomized design, with four replicates. Each replicate consisted of 50 gram of grains of each treatment, in which “moca” beans were removed by 11/64" x 3/4" sieves (oblong holes). Flattened grains were separated using sieves with round holes between 22/64" and 13/64" in diameter. Grains were collected in all experimental plots during May 2003, washed, peeled and dried in shadow conditions until reaching humidity of 12% (wet base). Parchment was removed and grain size and their variation according to different levels of fertilization was recorded after sifting. It was concluded that fertilization levels influenced the size of flattened grains of cultivars Catuaí, Icatu and Acaiá, and induced a general production of a greater proportion of large grains (screen > 17) in essay 2. However, grain size is affected not only by fertilization levels, but also by other factors as plant nutritional status and the amount of standing berries on the plants in the field. The percentage and number of “moca” berries in cultivars Rubi, Icatu and Acaia increased with the increase of fertilization level (essay 3) and seems to be related to lowconcentrations of Ca and P in leaves.